A new species of Dendropsophus (Anura, Hylidae) of the D. ruschii group from the Atlantic Forest in Serra da Mantiqueira, Minas Gerais, Brazil - Diego J. Santana; Donald B. Shepard; Priscila S. Carvalho; Márcia M. P. Müller; Clodoaldo L. Assis; Renato N. Feio (PLoS ONE, 2026)
The Dendropsophus ruschii species group currently comprises two species with disjunct distributions between the Atlantic Forest and the Amazon. Based on an integrative approach combining morphological, acoustic, and molecular data (mtDNA barcoding), we describe a new species from the Serra da Mantiqueira, Minas Gerais, Brazil. Dendropsophus liliae sp. nov. is diagnosed by its small size, rounded digital discs, presence of a calcar appendage, dark red iris, and a distinct white stripe from the snout to the upper eyelid. This discovery expands the known diversity of the group and represents its most inland record within the Atlantic Forest.